The effects of mind mapping activities on EFL students’ writing performance: A case at an upper secondary school : - Đặng, Thị Huyền Trân (Trường đại học Cần Thơ, 2018)
The research is an attempt to first investigate the effects of mind mapping on students' writing performance. The research also intends to determine the most influential and the least influential impact of mind mapping on improving students' writing ability. The purpose of this study is also conducted to know mind mapping can improve students' writing of the tenth grade students of a high school or not.